Mending life : a handbook for repairing clothes and hearts - Montenegro, Sonya; Montenegro, Nina (Sasquatch Books, 2020)
Mending Life encourages us to cherish our things by repairing them rather than discarding them. It also encourages us to change our consumption habits so that with small mends here and there, we extend the life of our garments and other household items. This handbook is for beginners but also offers more advanced techniques to those with some experience in mending. You'll learn basic techniques such as patching, but will have options to take it a step further with decorative sashiko stitching; you'll also learn how to darn socks and mend sweaters, as well as things like a tear in a bedsheet or down jacket. And along the way, the authors share heartfelt stories about the powerful act of mending, which strengthens not only the object we are repairing, but ourselves as well. Vibrant, full-color illustrations are woven throughout the handbook.